Respostas
respondido por:
1
pô Produtos Notáveis cara
(x²-2x+1)+(x²+4x+4)=x²+6x+9
(x²-2x+1)+(x²+4x+4)=x²+6x+9
respondido por:
1
(X-1)² + (X+2)² = (X+3)²
Utilizando propriedades do quadrado da soma e da diferença temos
(X² -2x + 1) + (x² + 4x + 4) = (X² + 6x + 9)
2x² + 2x +5 = X² + 6x + 9
2x² + 2x + 5 -x² -6x - 9 = 0
x² -4x -4 = 0
Utilizando propriedades do quadrado da soma e da diferença temos
(X² -2x + 1) + (x² + 4x + 4) = (X² + 6x + 9)
2x² + 2x +5 = X² + 6x + 9
2x² + 2x + 5 -x² -6x - 9 = 0
x² -4x -4 = 0
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás